PENERAPAN SISTEM MANAJEMEN KESEHATAN DAN KESELAMATAN KERJA DI RUMAH SAKIT - Demes Nurmayanti; Narwati .; Dealivy Hangga Arvin (JURNAL PENELITIAN KESEHATAN, 2014)
Hospital waste management do by labor with regard to occupational health and safety management system in the hospital. This research was descriptive research implemented in Rumkital Dr.Ramelan on the part Kesling and K3. The sample is committe organization of Kesling and K3. Research variable include the following the commitment and policy, planning, organizing and implementation. Primary data obtained through observation, open interviews and questionnaire. The research result obtained that 82% Health and Safety Work Management System RUMKITAL Dr. Ramelan on hospital waste management the stated value committe Kesling and K3 have been implemented good enough,consists of commitment and policy applied 82% good enough, planning applied 85% well, organizing applied 86% well, and implementation applied 80% good enough, stage of preparation 83% good enough, stage application 84% good enough, stage monitoring and evaluation good enough 84%, a review 71% good enough. Advice of this research is needs to be done comparative study with another hospital, composing visi on occupational health and safety, increasing the number of committe to avoid double job as well as handle the pattern and work process. Keywords: occupational health, safety management, system, hospital, occupational, health and safety, medical waste